Libraries, Building for the Future. Proceedings of the Library Buildings Institute and the American Library Trustee Association (ALTA) Workshop (Detroit, Michigan, July 1-3, 1965) - American Library Association, Chicago, IL.; Shaw, Robert J.; American Library Association, Chicago, IL. (Washington, D.C. : Distributed by ERIC Clearinghouse, 1967)
Included are the texts of all available papers given at the Institute and Workshop, as well as the presentations of the panelists and the discussions that ensued between members of the audience and the program speakers. Floor plans and similarly important illustrative materials are reproduced. The following sessions were included--(1) general session, (2) public library session, (3) college and university library sessions, (4) school library sessions, and (5) the American Library Trustee Association workshop. (RK)
Availability: American Library Association, 50 E. Huron Street, Chicago, Illinois 60611.
Sponsoring Agency: American Library Association, Chicago, IL. Library Administration Div.
Sponsoring Agency: American Library Trustee Association, Chicago, IL.
Microfiche.
Keywords: College Libraries; Community Relations; Educational Facilities Improvement; School Libraries; Building Plans; Facility Case Studies; Libraries; Library Planning